Multicultural Quality of Life Index in Relatives of People With Borderline Personality Disorder - Marco, Jose Heliodoro; Fernandez-Felipe, Isabel; García-Alandete, Joaquín; Fonseca-Baeza, Sara; Baños, Rosa M.; Garcia-Palacios, Azucena; Pérez Rodríguez, Sandra; Guillén, Verónica (Frontiers in Psychiatry, 2022)
Purpose The aim of the present study was to confirm the original factor structure of the Multicultural Quality of Life Index (MQLI) and analyze its psychometric properties in a sample of caregivers of people with borderline personality disorder (BPD). Methods The MQLI was administered to 233 relatives of people with BPD. Participants completed the MQLI, the Depression, Anxiety and Stress Scale (DASS-21), and the Connor-Davidson Resilience Scale (CD-RISC). Results Factor analysis of the relatives indicated that the MQLI generated a one-factor solution. The MQLI showed good internal consistency, ϖ = 0.91 [95% CI (0.90, 0.93)] and correlated significantly and positively with the CD-RISC (rs = 0.576) and negatively with the DASS-21 (rs = −0.583). Conclusion Consistent with other studies, the MQLI demonstrated feasibility, strong internal consistency, and good convergent and discriminant validity, which means it is a psychometrically robust measure for the assessment of quality of life in relatives of people with BPD. Along with other validation studies, this measure will be a useful tool for assessing quality of life in relatives of people with mental disorders.